Ifo World Economic Survey March 2003 - Gernot Nerb; Anna Stangl (Ifo World Economic Survey, 2003)
World Economic Climate: The current situation of the world economy remains unchanged - Inflation: No pickup of inflation expected in 2003 - Interest Rates: Downward trend of short-term and long-term interest rates expected to level off - Currencies: Major world currencies now close to sustainable equilibrium, although the UK pound still overvalued - Special Topic: WES experts in disagreement about the threat of widespread deflation at a global level. But clear signs of isolated deflationary tendencies in some countries.
Keywords: 330